Parenting and oral health in an inner-city environment: a qualitative pilot study - Shalini Nayee; Charlotte Klass; Gail Findlay; Jennifer E. Gallagher (BMC, 2018)
Abstract Background Preventable oral diseases such as dental caries remain common in the United Kingdom. Clustering of poor health is observed within deprived communities, such as inner-city areas, where elevated levels of dental need are associated with lower uptake of dental care. Successful oral health promotion (OHP) initiatives are contingent upon effective community engagement. The aim of this pilot study was to engage with families with young children to explore community views on oral health and dental care and thus tailor OHP initiatives more effectively to their needs. Methods Qualitative research, involving individual interviews and triad focus groups with parents/caregivers, was conducted in a south London inner-city community as part of a 'Well London' programme initiative. Results Seventeen parents/caregivers participated in this pilot study. Parents/caregivers described a spectrum of oral health behaviours based on their social history, past dental experiences and cultural influences. All parents described a clear desire to create healthy lives for their children; however, two broad groups were apparent, termed 'Oral Health Prioritisers' and 'Oral Health Non-prioritisers'. The former reported regularly accessing dental care for their children, believing that oral health contributes to systemic health. Non-prioritisers, however, preferentially used key services considered most beneficial to their child's wellbeing. Dental services were considered a low priority for this group, where oral health was synonymous with absence of pain. Participants in both groups favoured OHP initiatives involving a range of health and social care services, with schools at the epicentre of programmes. First-time parents were proposed as an important group requiring support in future OHP initiatives with evidence suggesting that first-born children may have delayed presentation to a dentist. Conclusions The findings suggest that this inner-city community may contain sub-groups with contrasting perspectives on oral health and oral health behaviours; nevertheless, there was support for a systems approach to oral health promotion initiatives involving a range of health and social care services, including a critcal role for schools, and actively connecting with first-time parents. The findings provide the basis for further research.